THE ROLE OF AGE IN MODERATING THE IMPACT OF EXTREME WEATHER ON MENTAL HEALTH AMONG PADDY FARMERS - Nurul Syazwani Ahmad Sabri; Siti Noorjannah Abd Halim; Marziah Zahar; Nur Yuhainis Ab Wahab; Muhammad Fadzly Zakaria (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Paddy farmers are frequently exposed to various environmental and occupational challenges. With over 485,000 workers in the agricultural sector, paddy farmers often face mental health risks due to unpredictable weather, long working hours, heavy physical labour, economic uncertainty, social isolation, exposure to hazardous chemicals and lack of access to mental health services. Older farmers may be more severely affected, making them more vulnerable to mental health issues. The objective of this study is to examine the relationship between extreme weather on the mental health of paddy farmers in Kedah, and to explore whether age moderates the relationship between extreme weather and mental health outcomes. The study employs a quantitative approach using purposive sampling. A questionnaire will be used to gather data on weather and the mental well-being of farmers. Statistical analysis will be conducted to understand the direct effects of independent variables (extreme weather) and the dependent variable (mental health), as well as the role of moderators (young vs older paddy farmers). The anticipated findings suggest that extreme weather might have a significant negative impact on the mental health of paddy farmers, irrespective of age. The moderating role of age might highlight that different age groups are affected by different mental health outcomes when exposed to extreme weathers. This study is expected to make a meaningful contribution to the development of more effective policies and strategies in improving the mental well-being of workers in the agricultural sector, thereby contributing to the overall safety and well-being of the people. This research aligns with the 8th Core of the National Security Policy 2021-2025, which emphasizes People’s Security, and supports Sustainable Development Goal (SDG) 3, which promotes mental health, and SDG 8, which encourages safe working environments.